2022
DOI: 10.1039/d2ma00390b
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of heteroatom-doped nanomaterial/core–shell nanostructure based electrocatalysts for fuel cells and metal-ion/air/sulfur batteries

Abstract: This review article deeply focuses on the use of heteroatom-doped nanomaterials and core–shell nanostructures for various kinds of fuel cell and battery applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 306 publications
0
5
0
Order By: Relevance
“…Using the following equation ( 1), all potentials were calibrated to a reversible hydrogen electrode [24,26].…”
Section: Catalyst Ink Preparation and Electrochemical Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the following equation ( 1), all potentials were calibrated to a reversible hydrogen electrode [24,26].…”
Section: Catalyst Ink Preparation and Electrochemical Measurementsmentioning
confidence: 99%
“…The Koutecky-Levich equation can be used to calculate the number of electron transfers per oxygen molecule involved in oxygen reduction based on Equations ( 2)-(4) [24,26].…”
Section: Catalyst Ink Preparation and Electrochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of this, it is necessary to develop efficient non-precious-metalgroup (non-PMG) bifunctional electrocatalysts employed in ZABs for the reasonable and effective energy utilization. [11][12][13] Recently, nitrogen-doped carbon (NC)supported transition metal materials, especially Fe-N X -C single-atom catalysts (SACs, x refers to the coordination number), have been widely investigated as one of the most promising electrocatalysts toward ORR and OER, which possess the advantages of cost-effectiveness, regulated atomic structure, outstanding electronic properties, and comparable catalytic activities to conventional platinum-metal-group (PMG) catalysts. [14,15] It has been widely reported that N-doped graphene is an ideal carrier for the anchorage and stability of Fe center by coordinating with 4 adjacent N atoms, forming Fe-N 4 sites in Fe-N X -C SACs to improve catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the theoretical researchers have examined the various pathways for ORR on surfaces of carbon based nanocatalysts to identify their active positions and suitable sites and to nd the possible pathways from thermodynamic and kinetics perspectives [13][14][15].…”
Section: Introductionmentioning
confidence: 99%